1996
DOI: 10.1080/00288233.1996.9513173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high rates of nitrogen fertiliser on white clover growth, morphology, and nitrogen fixation activity in grazed dairy pasture in northern New Zealand

Abstract: Nitrogen (N) fertiliser was applied to dairy pastures at nominal rates of 0, 200, or 400 kg N/ha per year on farmlets stocked at 3.24 (LS) or 4.53 (HS) Friesian cows/ha from June 1993 to June 1995. By June 1995, clover contents on farmlets LS200 and LS400 were 10.6 and 2.2%, respectively, compared with 16.8%onfarmletLS0. Most loss of clover on farmlets LS200 and LS400 occurred during the first 6 months of the trial when slow early-spring growth of clover combined with high N responses put clover at a competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
5
31
0
Order By: Relevance
“…only in the late spring summer-autumn period when clover growth was potentially more active, was it affected by N fertiliser. The depression in clover production at this time was most likely not a direct one of N fertiliser on the legume plant, but more an indirect result of the marked increase in grass Dm production in spring which shaded associated clover stolons and developing leaves during the period when clovers were commencing growth activity (harris & Thomas 1973;harris & Clark 1996;hepp et al 2003). This table 4 Statistical significance of nitrogen (N) fertiliser and soil phosphorus (P) effects on pasture grass dry matter production (kg Dm ha -1 ) in the late spring-autumn season (Nov-Apr) from 2000 to 2002 at each site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…only in the late spring summer-autumn period when clover growth was potentially more active, was it affected by N fertiliser. The depression in clover production at this time was most likely not a direct one of N fertiliser on the legume plant, but more an indirect result of the marked increase in grass Dm production in spring which shaded associated clover stolons and developing leaves during the period when clovers were commencing growth activity (harris & Thomas 1973;harris & Clark 1996;hepp et al 2003). This table 4 Statistical significance of nitrogen (N) fertiliser and soil phosphorus (P) effects on pasture grass dry matter production (kg Dm ha -1 ) in the late spring-autumn season (Nov-Apr) from 2000 to 2002 at each site.…”
Section: Discussionmentioning
confidence: 99%
“…in comparison, responses by clover to N fertiliser application rarely occur unless Rhizobia activity is inhibited or new pastures are in the early stages of establishment (Cullen 1969), when low rates of N fertiliser (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) kg N/ha) have been shown to be beneficial. Application of higher rates of N, such as used in dairying (Ball & Field 1982;harris & Clark 1996), or repeated applications of N (e.g., eight applications of 50 kg N ha -1 ), can cause a decline in clover content and production. The most commonly reported effect of nitrogen fertiliser application on pasture legumes is a depression in clover density and yield (ledgard & Saunders 1982;Caradus et al 1993), whereas other reports (o'Connor & Gregg 1971;Crush et al 1982) indicate no deleterious effects on clover production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated applications of N fertilizer has been associated with a reduction in the legume components of pasture (Bolland and Guthridge 2007). However, other reports have identified that when stocking rate was at levels that prevented competition between grasses and legumes the application of N fertilizer has a minimal effect on the persistence of legumes in pastures (Harris andClark 1996, McKenzie et al 2003). It is clear that reducing N applications favours the legume component of pastures (Turner et al 2013).…”
Section: Management Of Simple and Diverse Pasturesmentioning
confidence: 99%
“…Further evidence to support these claims on a general negative correlation of mineral N use on clover swards has been documented. Harris and Clark (1996) reported that for mixtures of perennial ryegrass and white clover treatments that did not receive N fertilizer at low and high stocking rates had a mean clover proportion of 16.5% during their trial with maximum clover proportion in late summer. Mineral N application in their study caused a large decrease in clover proportion on low stocking rate treatments 10.6 and 2.2% that received 200 or 400 kg N ha -1 respectively and clover yield was lower on all treatments that had received N fertilizer (Harris and Clark, 1996).…”
Section: Growth and Persistencementioning
confidence: 99%